Beyond science : the wider human context - Polkinghorne, J. C., 1930-2021 (Cambridge University Press, 1996)
"Science is very successful in discovering the structure and history of the physical world. However, there is more to be told of the encounter with reality, including the nature of scientific inquiry itself, than can be gained from impersonal experience and experimental test alone. Beyond Science considers the human context in which science operates and pursues that wider understanding which we all seek. It looks to issues of meaning and value, intrinsic to scientific practice but excluded from science's consideration by its own self-denying ordinance. The author raises the question of the significance of the deep mathematical intelligibility of the physical world and its anthropically fruitful history. He considers how we may find responsible ways to use the power that science places in human hands. Science is portrayed as an activity of individuals, pursued within a convivial and truth-seeking community." "This book neither overvalues science (as if it were the only worthwhile source of knowledge) nor devalues it (as if it were to be treated with suspicion or not taken seriously). Rather, Beyond Science provides a considered and balanced account that firmly asserts science's place in human culture, maintained in mutually illuminating relationships with other aspects of that culture."--Jacket